Advancing self-regulated learning strategies through interactive e-learning community (iELC) - Vighnarajah; Wong, Su Luan; Abu Bakar, Kamariah (2007)
The interactive e-Iearning community (iELC) discussion platform attempts to advance the World Wide Web (WWW) as an extension of teaching technology to develop better self-regulated learning strategies. The iELC assimilates both traditional and online classroom advantages. Hence, self-regulated learning strategies are practiced through synchronous discussion in classrooms and asynchronous discussion in iELC forums. This paper examines development of self-regulated learning strategies through participation in iELC discussion platform. Learners with effective self-regulated learning skills are better at managing their learning process. The Solomon-Four Group research design was employed for the study. Samples (n = 102) consisted of Form Four Physics KBSM students from regular national secondary schools in Kuala Lumpur. The Motivated Strategies for Learning Questionnaire (MSLQ) was used to measure the samples' use of self-regulated learning strategies. Two-way analysis of variance was conducted to explore the impact of two independent factors (iELC treatment and administration of pretest) on one dependent variable (self-regulated learning posttest mean scores). This paper highlights on the statistically significant main effect for the IRC treatment [F (1, 98) = 17.92, p=.000], and this effect size was big (eta-squared=0.16). This result indicates that participation in iELC discussion platform is able to significantly develop better self-regulated learning strategies compared to traditional classroom setting.